A Descriptive Study of Family Transitional Care for Patients with Cardiovascular Disease - Kezia Wahyudi; Bintang Oktavia; Greatisa Pea; Lani Watania; Heman Pailak (GLOBAL HEALTH SCIENCE GROUP, 2024)
Cardiovascular disease is a disease with the highest percentage of non-communicable diseases that cause death worldwide. Several cardiovascular diseases such as hypertension, coronary heart disease, heart failure, and myocardial infarction require the same ongoing care plan, both in the hospital and at home. Transitional care is very important for patients with cardiovascular disease and the management post hospitalization is conscientious to prevent re-hospitalization. Objective : This study aims to describe the care transition of families of patients with cardiovascular disease to post-hospitalization. Method: The research design uses quantitative research with descriptive methods. The research was conducted in January - April 2023 using the accidental sampling technique with total of 78 respondents at the Tangerang Private Hospital using the Family Caregiver Activation in Transitions Tool (FCAT) instrument. Data were analyzed using univariate analysis. Results: The results showed ¬that most of the respondents (55.2%) had high or good transitional care. While others (44.9%) are in the low category. Conclusions : The ideal transitional care needs multidisciplinary teams to collaborate. Nurses play a crucial part in the discharge process by coordinating care and communicating with significant parties such as families and community providers to facilitate smooth transfers of care. Further study related to nurses' abilities to deliver appropriate transitional care is also required in the future.